2019
DOI: 10.1007/s12015-019-09925-z
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Administration of Human Liver Stem Cells in Infants with Inherited Neonatal-Onset Hyperammonemia: A Phase I Study

Abstract: Previous studies have shown that human liver stem-like cells (HLSCs) may undergo differentiation in vitro into urea producing hepatocytes and in vivo may sustain liver function in models of experimentally induced acute liver injury. The aim of this study was to assess the safety of HLSCs intrahepatic administration in inherited neonatal-onset hyperammonemia. The study was approved by the Agenzia Italiana del Farmaco on favorable opinion of the Italian Institute of Health as an open-label, prospective, uncontro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…When seeded in acellular liver scaffold, HLSC were shown to differentiate into mature functional hepatocytes [ 9 ]. More recently, a phase 1 study demonstrated the safety of HLSC administration in infants with neonatal hyperammonemia [ 10 ]. Growing evidence supports the hypothesis that the biological effects of stem cells on neighboring cells are mediated by paracrine mechanisms related to the release of soluble factors and extracellular vesicles (EV) [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…When seeded in acellular liver scaffold, HLSC were shown to differentiate into mature functional hepatocytes [ 9 ]. More recently, a phase 1 study demonstrated the safety of HLSC administration in infants with neonatal hyperammonemia [ 10 ]. Growing evidence supports the hypothesis that the biological effects of stem cells on neighboring cells are mediated by paracrine mechanisms related to the release of soluble factors and extracellular vesicles (EV) [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, that there are discrepancies in the data presented by authors in the literature concerning the pattern of markers expressed by epithelial and mesenchymal afterbirth cells [109,181]. Native human afterbirth cells share some phenotypic features comparable with human hepatic multipotent stem cells (hHpSC) and bipotent hepatoblasts: EpCAM, CK19, CD133 [17,27,35,181], adult multipotent stem cells expressing mesenchymal markers: CD44, CD73, CD90, CD105, CK19, SSEA-4, NANOG, OCT-4 [15,52,66,67,181,[53][54][55][56][57][58][59][60] and adult bipotent hepatic progenitor cells (HPC): DLK-1 [78,184]. EpCAM expression, characteristic of hepatoblasts, but not of mesenchymal liver cells, has been confirmed in afterbirth cells only in few studies [181,[183][184][185].…”
Section: Discussionmentioning
confidence: 97%
“…In vitro liver mesenchymal stem cells divide intensively reaching the confluence required for passage after about 3-5 days of culture. They are able to differentiate in vitro not only towards the hepatocytic lineage [ 52 , 59 , 60 , 64 , 65 ], but also osteocytic [ 52 , 59 , 65 ], chondrocytic [ 61 ], endothelial [ 52 , 53 ] lineages, and insulin-producing islet cells of the pancreas [ 52 , 56 ], but not to the adipocytic lineage [ 52 , 59 , 61 ]. On the other hand, one study demonstrated that liver mesenchymal stem cells are able the differentiate into adipocyte-like cells [ 65 ].…”
Section: Liver Development and Regenerationmentioning
confidence: 99%
See 2 more Smart Citations